2012
DOI: 10.1007/s10508-012-9945-3
|View full text |Cite
|
Sign up to set email alerts
|

Eye Fixations Indicate Men’s Preference for Female Breasts or Buttocks

Abstract: Evolutionary psychologists have been interested in male preferences for particular female traits that are thought to signal health and reproductive potential. While the majority of studies have focused on what makes specific body traits attractive-such as the waist-to-hip ratio, the body mass index, and breasts shape and size-there is little empirical research that has examined individual differences in male preferences for specific traits (e.g., favoring breasts over buttocks). The current study begins to fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…These results are consistent with the study of Krantz, Bailard, and Scher (1997), which revealed that men prefer larger breasts than women. Other studies also reported a general male preference for larger breasts (Dagnino et al, 2012;Singh & Young, 1995). Although the mate selection theory failed to explain this gender difference, our results still indicate that both genders agree in preference for breasts larger than the judged average (see Figure 4).…”
Section: Males -Femalessupporting
confidence: 43%
See 3 more Smart Citations
“…These results are consistent with the study of Krantz, Bailard, and Scher (1997), which revealed that men prefer larger breasts than women. Other studies also reported a general male preference for larger breasts (Dagnino et al, 2012;Singh & Young, 1995). Although the mate selection theory failed to explain this gender difference, our results still indicate that both genders agree in preference for breasts larger than the judged average (see Figure 4).…”
Section: Males -Femalessupporting
confidence: 43%
“…Investigating individual differences in the male preference between breasts and buttocks, Dagnino, Navajas and Sigman (2012) found bimodal distribution of preference, albeit skewed towards buttocks as contributors to their choice. Some studies revealed cultural and ethnic differences in the preference for large buttocks.…”
Section: Buttocks Sizementioning
confidence: 99%
See 2 more Smart Citations
“…Men with ideal body shapes might be seen as more attractive and research shows that attractiveness predicts focus on sexual body parts (Dagnino, Navajas, & Sigman, 2012). Consistently, Gervais, et al (2012) found that men's bodies with ideal body shapes were seen as more interchangeable (i.e., another indicator of objectification) compared to men's bodies with less ideal and average body shapes.…”
Section: Appearance-focus Increases the Objectifying Gaze Toward Menmentioning
confidence: 82%